Isolated atrophy and fatty infiltration of supraspinatus: A rare finding. Issue 3 (19th December 2018) - Hughes, Peter; Miranda, Rhian; Boyer, Lucinda
Summary: Isolated atrophy and fatty infiltration of supraspinatus is very rare. We report the case of a 53 year old male with isolated atrophy and complete fatty replacement of supraspinatus and discuss potential aetiologies.